The Effect of Work Experience, Training, Career Development, and Commitment on Employee Performance at Panai Hulu District Office Tanjung Sarang Elang - Dodi Kamayandi Sitepu; Mulya Rafika; Abd Halim (PT Mattawang Mediatama Solution, 2023)
This study aims to analyze the influence of work experience, training, career development and commitment to employee performance at the Panai Hulu sub-district office, Tanjung Sarang Elang. The research method used in this research is quantitative. In this study, the population was 40 employees of the Panai Hulu Sub-district Office, Tanjung Sarang Elang. The research sample used a saturated sampling technique by attracting the entire existing population to be used as a research sample with a total of 40 people. Data collection techniques used were observation, documentation studies and questionnaires. The method of analysis of this research is multiple linear regression with the SPSS program. The results of the study prove that work experience has a positive and significant effect on employee performance at the Panai Hulu Tanjung Sarang Elang sub-district office. Training has a positive and significant effect on employee performance at the Panai Hulu Sub-district Office, Tanjung Sarang Elang. Career Development has a positive and significant effect on Employee Performance at the Panai Hulu Sub-district Office, Tanjung Sarang Elang. Commitment has a positive and significant effect on employee performance at the Panai Hulu Sub-district Office, Tanjung Sarang Elang. Work Experience, Training, Career Development and Commitment simultaneously have a positive and significant effect on Employee Performance at the Panai Hulu Sub-district Office, Tanjung Sarang Elang. The coefficient of determination is 0.837, meaning that employee performance can be explained by the variables Work Experience (X1), Training (X2), Career Development (X3) and Commitment (X4) of 83.7%, while the remaining 16.3% can be explained by other variables which were not examined in this study.